Psychological combustion and its relationship to self-disclosure in primary school teachers - Hashem Muhammad Al-Saadi, Ayad (International Journal of Psychosocial Rehabilitation, 2020)
To achieve the objectives of the research, the researcher adopted the measure of psychological combustion of (Al-Hatmi, 2014) and the building of the self-disclosure measure according to the theory of social penetration of (Altman * Taylor,1973), and applied the two measures to the sample of the research consisting of (400) teachers of the Directorate of Education of the Eastern Parties of Baghdad, after they were selected in the random class way, and determine the number of teachers and teachers proportionally. After examining the study data statistically using (T-test for one sample, T-test for two independent samples, Pearson correlation coefficient, Alpha Kronbach equation, and adultery test), the research found the following results: the research sample members had a high psychological combustion level compared to On the theoretical average of the scale, the research sample members have a high level of self-disclosure compared to the theoretical average of the scale, there are no statistically significant differences in the correlation between psychological combustion and self-disclosure according to the Gender variable (male and female), there is a relationship with A statistical indication between psychological combustion and self-disclosure and in the light of these results the research came up with a set of recommendations and suggestions.